SOX4 expression is associated with treatment failure and chemoradioresistance in oral squamous cell carcinoma. Issue 1 (December 2015) - Yoon, Tae; Kim, Sun-Ae; Cho, Wan; Lee, Dong; Lee, Joon; Park, Young-Lan; Lee, Kyung-Hwa; Lee, Jae; Kweon, Sun-Seog; Chung, Ik-Joo; Lim, Sang; Joo, Young-Eun
Abstract Background In humans, sex-determining region-Y (SRY) related high-mobility-group box 4 (SOX4) is linked to development and tumorigenesis. SOX4 is over-expressed in several cancers and has prognostic significance. This study evaluated whether SOX4 affects oncogenic behavior and chemoradiotherapy response in head and neck squamous cell carcinoma (HNSCC) cells, and documented the relationship between its expression and prognosis in oral squamous cell carcinoma (OSCC). Methods We used small interfering RNA in HNSCC cells to evaluate the effect of SOX4 on cell proliferation, apoptosis, chemoradiation-induced apoptosis, invasion, and migration. SOX4 expression in OSCC tissues was investigated by immunohistochemistry. Results SOX4 knockdown (KO) decreased cell proliferation and induced apoptosis by activating caspases-3 and −7, and poly-ADP ribose polymerase and suppressing X-linked inhibitor of apoptosis protein in HNSCC cells; it also enhanced radiation/cisplatin-induced apoptosis; and suppressed tumor cell invasion and migration. Immunostaining showed SOX4 protein was significantly increased in OSCC tissues compared with adjacent normal mucosa. SOX4 expression was observed in 51.8 % of 85 OSCC tissues, and was significantly correlated with treatment failure (P = 0.032) and shorter overall survival (P = 0.036) in patients with OSCC. Conclusions SOX4 may contribute to oncogenic phenotypes of HNSCC cells by promoting cell survival and causing chemoradioresistance. It could be a potential prognostic marker for OSCC.